How to Design and Fabricate a Sugarcane Bud Chipping Machine with a Foot Pedal - Samah, Smith; Olabisi, Samuel A. (Bumi Publikasi Nusantara, 2024)
This Project aims to design and fabricate a Sugarcane Bud Chipping Machine. It has been observed that farmers prefer to plant sugarcane directly in the field manually, which is a cumbersome and time-consuming process. Once the problem was identified, an approach was conceptualized to provide a solution. Sugarcane Bud Chipper which cuts the sugarcane buds in smaller sizes for plantation purposes. These buds are smaller than the sugarcane sticks from earlier plantation methods. This machine incorporates various components, assembled uniquely for a desirable output. The power needed to cut the sugarcane bud is generated from the pedal through human effort. A chain, 137 cm long, was used to link the two sprockets, one was attached to the pedal, while the other sprocket was attached to the arm of the cutting blade. The two sprockets are coupled to two shafts, which transfer force to the arm of the cutting blade. When the pedal is been paddled, mechanical energy leaves the pedal to the cutting unit. The blade holder was attached to the arm of the cutting blade. When the pedal is pressed, the shaft slickly rotates, the cutting unit moves downward and when the pedal is released, the cutting unit returns, upward through the support of the spring. The pedal-powered Sugarcane Bud Chipping Machine is easy to operate and reduces intensive labor. This machine makes operation easier and more comfortable in the process of sugarcane production for rural dwellers who do not have access to a power supply. The use of this machine will improve the economic well-being of local farmers in remote areas.